Enhanced Hydrologic Connectivity and Solute Dynamics Following Wildfire and Drought in a Contaminated Temperate Peatland Catchment - Marcotte, Abbey L.; Limpens, Juul; Nunes, João Pedro; Howard, Ben C.; Hurley, Alexander G.; Khamis, Kieran; Krause, Stefan; Croghan, Danny; Kourmouli, Angeliki; Leader, Samantha; Singh, Tanu; Stoof, Cathelijne R.; et al. (Water resources research, 2024)
Intact peatlands provide hydrological ecosystem services, such as regulating water regimes and immobilizing pollutants within catchments. Climate change impacts including drought and wildfire may impair their functioning, potentially impacting ecosystem service delivery. Here we investigate stream water quality changes following the combined impacts of a summer drought and wildfire in a peat‐dominated catchment in the UK during 2018. The study catchment stores legacy pollutants (i.e., metals) due to past industrial activity, thus making it particularly susceptible to pollutant release during wildfires. We quantified changes in water chemistry during five storm events over a 9‐month period following the wildfire. Concentration‐discharge (C‐Q) relationships for nine solutes were analyzed to explore changes in activation and connectivity of solute source zones. Hysteresis and flushing indices of C‐Q responses further described solute dynamics during storm events. We found that most nutrient and base cation concentrations in the stream discharge were highest in the immediate post‐fire storm events and decreased during subsequent autumn and spring storms. Metal concentrations increased during autumn and spring storms, indicating delayed mobilization from within‐peat or distal headwater sources. Our findings suggest that seasonal re‐wetting and hydrologic connectivity following disturbance influenced solute source zone activation and transport in the study catchment. Water quality responses associated with wildfire and drought were primarily observed in the months following the wildfire, suggesting mobilization of pollutants peaks shortly after fire. Our results contribute to a critical understanding of the future of water quality risks in temperate peatland catchments subject to disturbances exacerbated by climate change. Plain Language Summary Peatlands are defined by their accumulated organic matter, providing valuable natural services such as storing carbon, and regulating climate, water quality and runoff. Such capability may be reduced when peatlands are impacted by extreme wildfires and droughts. We studied impacts of a severe wildfire and drought on stream water quality in a peatland catchment in the UK, within a region that may be more frequently impacted by these events in the future due to changing climate. This peatland also stores pollutants (namely metals emitted and retained during the industrial revolution), further enhancing risks to drinking water quality. We determined how the wildfire affected instream chemistry post‐fire, and how nutrients and metals moved through the catchment. We found that levels of nutrients in the stream flow increased immediately after the wildfire, followed by a decrease with time. However, the levels of metals increased during the following autumn and spring. This suggests that metals were released later and came from different parts of the catchment compared to the nutrients. Our results show that following the fire, the way water flowed through the catchment played an important role in how substances were transported. The impacts on water quality were most pronounced in the first months post‐wildfire and seemed to be short‐lived. Key Points Nutrients and base cation streamflow concentrations were elevated following wildfire, and decreased in autumn and spring storm events Metals in the catchment showed delayed mobilization, indicating distal headwater source zones rather than proximal to stream sources Seasonal re‐wetting after drought enhanced catchment hydrologic connectivity, influencing source zone activation and transport